The search for preoperative biomarkers for thyroid carcinoma: application of the thyroid circadian clock properties. (March 2017) - Dibner, Charna; Sadowski, Samira Mercedes; Triponez, Frederic; Philippe, Jacques
Accumulating evidence suggests that alterations in the molecular clocks underlying the circadian time-keeping system might be connected to changes in cell cycle, resulting in oncogenic transformation. The hypothalamic–pituitary–thyroid axis is driven by a circadian clock at several levels, with an endocrine feedback loop regulating thyroid-stimulating hormone. Changes in the expression levels of circadian and cell cycle markers may correlate with clinic-pathological characteristics in differentiated follicular thyroid carcinomas. Here we summarize recent advances in exploring complex regulation of the thyroid gland transcriptome and function by the circadian oscillator. We particularly focus on clinical implications of the parallel assessment of the circadian clock, cell-cycle and cell functionality markers in human thyroid tissue, which might help improving preoperative diagnostics of thyroid malignancies.